PENINGKATAN KUALITAS LAYANAN PUBLIK DI STASIUN MADIUN SAAT LIBUR NATARU MELALUI EVALUASI SERVQUAL - Leliana, Arinda; Apriliani, Nurul Fitria; Puspitasari, Armyta; Pramudhita, Salsa Alya (Jurnal Abdi Insani, 2025)
During the Christmas and New Year (Nataru) holiday period, Madiun Station experiences a substantial increase in passenger volume compared to regular operational days. This circumstance necessitates enhancements in service quality to align with customer expectations. Through a SERVQUAL-based evaluation, this initiative seeks to identify service gaps and develop targeted improvements. These efforts are intended to reinforce public trust in the quality and reliability of railway transportation services. This study aims to evaluate customer satisfaction at Madiun Railway Station during the 2024 Christmas and 2025 New Year holiday period, a time of significantly increased passenger volume. Using the SERVQUAL method, five key service quality dimensions Tangibles, Reliability, Responsiveness, Assurance, and Empathy were assessed to measure the gap between customer expectations and perceptions. A total of 240 respondents participated in the survey. The results revealed a positive gap in all dimensions, indicating that customer expectations exceeded the services received. The largest gap was found in the Empathy dimension (0.184), followed by Tangibles (0.139), suggesting an urgent need for improvements in personal interaction and physical facilities. A paired t-test confirmed a statistically significant difference between expectations and perceptions (p-value = 0.00018). Based on the findings, it is recommended that station management improve staff training on empathetic service, modernize physical infrastructure, and utilize digital tools to enhance customer experience. This research provides practical insights for enhancing service quality and contributes to the ongoing development of public transportation service standards in Indonesia.